gossypiin - Imhotep, Malika Ra (Book collections on Project MUSE., 2022)
"Gossypiin is a Black feminist hypertext that registers the feeling of an experience of the world in which the self is an unstable plurality continuously unmade. It is a story marked into the flesh of the poet, transferred onto the page through a process of distillation. It is an enactment of Black feminist poetic utterance that tends to the inside parts. This harvest of poems is inspired by the plant medicine latent in Gossypium Herbaceum, or Cotton Root Bark, which was used by enslaved Black women to induce labor, cure reproductive ailments, and end unwanted pregnancies. Through an arrangement of stories and memories experienced, read, heard, reimagined, and remixed, the poet reckons with a peculiar yet commonplace inheritance of violation and survival. gossypiin performs an interruption of the narrative silence around sexual harm and the mark it makes on Black femme subjectivity"--